A borehole investigation of zircon radiation damage annealing. (29th April 2019) - Jonckheere, Raymond; Heinz, Daniel; Hacker, Bradley R.; Rafaja, David; Ratschbacher, Lothar
Abstract: This contribution reports Raman radiation damage measurements of zircons from the Kontinentale Tiefbohrung, on the western border of the Bohemian Massif. The mean wavenumbers ( ω 3 ) and widths (Γ3 ) of the ν 3 (SiO4 ) Raman band are constant down to 3 km, decrease ( ω 3 ) resp. increase (Γ3 ) between 3 and 5 km, and are again constant between 5 and 7 km. Uniform high Γ3 values associated with ω 3 values close to those of undamaged zircon between 5 and 7 km are interpreted as due to residual damage predating the exhumation of the Bohemian Massif. A superimposed post‐exhumation signal indicates full damage retention down to 3 km depth, partial annealing between 3 and 5 km, and zero retention at greater depth. An attempt to calculate radiation damage ages gives results of a meaningful order of magnitude but also exposes difficulties associated with dating basement samples with complex damage accumulation and annealing histories.